The Validity of A Will Made Before A Notary Without The Knowledge of The Heirs of The Will - Muhammad Ihza Prayogo; Soemali (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2025)
Making a will is very useful because it provides clarity on the property left by the owner when he dies. There is a case in the Supreme Court Decision Number: 3658 K/PDT/2022, where the Plaintiff as a Sinshe claimed to have received a will from a patient who had died, while the heirs of the patient were completely unaware of the making of the Will. Based on this, this study analyzes the recipient of the will whose position is as a sinshe or medical expert in receiving a will from the patient he treated, and analyzes and explains the validity of the will deed made before a notary without the knowledge of the heirs of the testator in the Supreme Court jurisprudence Number: 3658 K/PDT/2022. This type of research is normative legal research, with a statutory approach, a conceptual approach, and a case approach. That in accordance with the provisions of Article 906 of the Civil Code, the recipient of the will whose position is as a sinshe or medical expert is not allowed to receive a will from the patient he treated. The validity of a will made before a notary without the knowledge of the heirs of the testator is null and void and has no binding legal force.